2011
DOI: 10.1177/0266242610375703
|View full text |Cite
|
Sign up to set email alerts
|

The role of IT competences in gaining value from e-business: An SME case study

Abstract: Many SMEs have been slow to exploit the potential of e-business. However, it can be difficult for any firm to gain value from e-business, and particularly so for SMEs that may lack important information technology (IT) competences. The study focused on one SME which had undertaken a series of e-business initiatives over a period of 10 years. The analysis revealed that the firm used e-business in two different ways: e-business for innovation, and e-business for integrating business processes. Four IT competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 35 publications
1
58
0
1
Order By: Relevance
“…In fact, limited financial resources cause SMEs to provide less training to their employees which leads to insufficient ICT expertise within the organization (Windrum and Berranger, 2002). Although SMEs face resource limitations, some argue that they should not ignore the significance of ICT but instead embrace new technologies in their businesses to obtain greater value through e-Business usage (Ashurt et al, 2011). Lin (2007) claims that organizational learning is crucial to the process of adopting new technologies in an organization.…”
Section: Organizationalmentioning
confidence: 99%
“…In fact, limited financial resources cause SMEs to provide less training to their employees which leads to insufficient ICT expertise within the organization (Windrum and Berranger, 2002). Although SMEs face resource limitations, some argue that they should not ignore the significance of ICT but instead embrace new technologies in their businesses to obtain greater value through e-Business usage (Ashurt et al, 2011). Lin (2007) claims that organizational learning is crucial to the process of adopting new technologies in an organization.…”
Section: Organizationalmentioning
confidence: 99%
“…In the context of SMEs, Ashurst, Cragg, and Herring () found that IT competence is one of the most important competitive advantages because of the vital role it plays in ensuring an accurate flow of information about product and financial status that reflects the critical status of the supply chain. The result of an empirical study by Tippins and Sohi (), however, suggests that firms looking for strategic advantage should not only develop IT competency but also should simultaneously focus on organizational culture and organizational learning.…”
Section: Enhancing Competitiveness With It Competencementioning
confidence: 99%
“…Although small businesses make an important contribution to national economies, their effective use of ICT could improve their contribution (Kapurubandara, 2009) and benefits can potentially be obtained from ICT use to 'transform' businesses (Alonso Mendo & Fitzgerald, 2005). However, small businesses have typically not gained the value from their online presence that might have been expected (Ashurst et al, 2011).…”
Section: Introductionmentioning
confidence: 99%